Identification of new anti-Candida compounds by ligand-based pharmacophore virtual screening. (1st November 2016) - Gidaro, Maria Concetta; Alcaro, Stefano; Secci, Daniela; Rivanera, Daniela; Mollica, Adriano; Agamennone, Mariangela; Giampietro, Letizia; Carradori, Simone
Abstract: Candida albicans represents the most prevalent microbial population in mucosal and systemic infections, usually confined to severely immunocompromised people. Considering the increase of resistant strains and the demand for new antifungal drugs endowed with innovative mechanism of action, we performed a ligand-based virtual screening in order to identify new anti- Candida compounds. Starting from a large library of natural/semisynthetic products and several published synthesized compounds, three coumarin derivatives were discovered in silico as new hit compounds and submitted to the in vitro assay in order to confirm their predicted biological activity.